Evaluation of Silica Gel Performance Used in Power Distribution Stations - Saad M. Potrous (Progress in Chemical Science Research Vol. 6, 2023)
Silica Gel material is used as absorbent material because its crystal structure consisting of large molecules with large surface areas and low density and used as a catalyst for chemical reactions due to adding the acidic qualities. This material can also be used in many technical applications such as industrial equipment because it is characterized by a high affinity for absorbing gases and water vapor. Where used in industrial equipment, operating units, oil refineries and electrical transformers. This work was studied the efficiency of this material where used in secondary transformers with high conversion adapters for electrical power distribution networks are used as absorbent material to water vapor generated during the operation of the equipment or wet weather with high relative humidity. Results showed that the efficiency of absorption Silica Gel material is reduced during frequent use in secondary transformers as the re-dried for 5- stages experiments of this research after saturation moisture for use again in adapters lead to lack of usability on the absorption. The appropriate solutions to re-use this material efficiently so as to avoid technical problems in secondary transformers due to increased humidity inside the converted, leading to major damage and the stoppage of work of these equipments.